Exogenous Supplementation of Silicon Improved the Recovery of Hyperhydric Shoots in Dianthus caryophyllus L. by Stabilizing the Physiology and Protein Expression - Soundararajan, Prabhakaran; Manivannan, Abinaya; Cho, Yoon S.; Jeong, Byoung R. (Frontiers in Plant Science, 2017)
Hyperhydricity is one of the major problems hindering in vitro propagation of Dianthus caryophyllus L. Silicon (Si) is a well-known beneficial element renowned for its stress amelioration properties in plants. This study has demonstrated the physiological and molecular mechanism behind the Si-mediated recovery from hyperhydricity in D. caryophyllus L. ‘Green Beauty’. Four weeks old hyperhydric shoots obtained from temporary immersion system were cultured on the Murashige and Skoog (MS) medium supplemented with 0 (control), 1.8 mM, or 3.6 mM of potassium silicate (K2SiO3). After two weeks of culture, we observed only 20% of hyperhydric shoots were recovered in control. On the other hand hyperhydricity, shoot recovery percentage in 1.8 mM and 3.6 mM of Si were 44% and 36%, respectively. Shoots in control possessed higher lipid peroxidation rate compared to the Si treatments. Similarly, damaged stomata were detected in the control, while Si treatments restored the normal stomatal development. Expressions of superoxide dismutase, guaiacol peroxidase, and catalase varied between the control and Si treatments. Furthermore, a proteomic analysis showed that as compared with the control Si up-regulated 17 and 10 protein spots in abundance at 1.8 mM and 3.6 mM of Si, respectively. In comparison to the 3.6 mM, 1.8 mM of Si treatment up-regulated 19 proteins and down-regulated 7 proteins. Identified proteins were categorized into six groups according to their biological roles such as ribosomal binding, oxido-reduction, hormone/cell signaling, metal/ion binding, defense, and photosynthesis. The proteomic results revealed that Si actively involved in the various metabolisms to accelerate the recovery of the shoots from hyperhydricity. Thus, the outcomes of this study can be utilized for addressing the molecular insight of hyperhydricity and its recovery mechanism by the supplementation of Si. Therefore, we conclude that active involvement of Si in the regulation and signaling process of proteins at 1.8 mM concentration could be efficient to trigger the reclamation process of hyperhydric carnation shoots.